Modeling The Determinants of Stigma Among Women of Childbearing Age (15-49 Years) Toward People Living With HIV in East Kalimantan Province - Nurjannah, Siti; Anggraeni, Ike; Andi Baso, Ismail (Universitas Mulawarman, 2024)
The negative stigma attached to people living with HIV/AIDS makes people reluctant to take an HIV test for fear of positive results and fears of rejection by their potential sexual partners. This stigma occurs because of lack of knowledge and mass media/information exposure about HIV/AIDS. The study aimed to obtain a binary logistic regression prediction model and determinant that influence the stigma of eligible women (15-49 years) against people living with HIV/AIDS in East Kalimantan Province. The study used a cross sectional study design and data analysis method with binary logistic regression. This study employed data from the Indonesian Demographic and Health Survey (IDHS) 2017 with 1096 sample. Study result showed 53% eligible woman had a high stigma. Knowledge and marital status has a significant effect on stigma towards people living with HIV/AIDS. The result of Binary Logistic Regression model revealed g(x) = 0.096+ 0.578 (knowledge) – 0.329 (marital status). The model is in accordance with the predictor variables entered into the model, It can explain 3,4 percent diversity and has a 57,2 percent classification accuracy. Therefore are need knowledge improvement and the positive stigma against people living with HIV/AIDS to reduce the stigma towards people living with HIV/AIDS